Treatment of malignant superior vena cava syndrome by endovascular stent insertion: Experience on 52 patients with lung cancer - Urruticoechea, A.; Mesı́a, R.; Domı́nguez, J.; Falo, C.; Escalante, E.; Montes, A.; Sancho, C.; Cardenal, F.; Majem, M.; Germà, J.R. (Lung cancer (Amsterdam, Netherlands), 2004)
Background: Superior vena cava syndrome (SVCS) is a frequent presentation of malignancies involving the mediastinum and can seriously compromise treatment options and prognosis. Stenting of superior vena cava is a well-known but not so commonly used technique to alleviate this syndrome. Patients and methods: Between August 1993 and December 2000 we performed 52 stenting procedures in patients affected by non-small cell lung cancer (NSCLC). Results: Phlebographic resolution of the obstruction was achieved in 100% of cases with symptomatic and subjective improvement in more than 80%. One major complication was observed due to bleeding during anticoagulation. Re-obstruction of the stent occurred in only 17% of the cases, the majority due to disease progression. Improvement of the syndrome allowed hydration necessary for full dose platinum treatment when indicated in patients affected by lung cancer. Conclusions: Stenting of the superior vena cava syndrome is a safe and effective procedure achieving a rapid alleviation of symptoms in almost all patients, and allowing for full dose treatment in lung cancer patients. This procedure could change the traditional poorer prognosis attributed to non-small cell lung cancer patients presenting with this syndrome.